Treatment of natural coccidial infection in Lambs using Monensin - AYENI, A. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The therapeutic effect of monensin on natural coccidial infection was tested in two trials. Lambs with heavy mixed infections were fed a diet containing 20g monensin/tonne over a period of 14 days. In both trials and over period of 35 days, coccidial oocyst output in non-medicated lambs was reduced by 53.6%. In the medicated lambs, it was practically nil. Monenzin thus appears to have some therapeutic effect on sheep coccidiosis.